Development of an intervention to support parents receiving treatment in psychiatric inpatient hospital using participatory design methods - Dunn, Abby; Fenton, Patrick; Cartwright-Hatton, Sam (Frontiers in Psychiatry, 2024)
When parents of dependent children are treated in psychiatric inpatient hospital, it typically involves separation of parent and child for the duration of treatment, which can be highly distressing to the dyad and can result in disruption to the parent-child relationship. Parents who have experienced hospitalisation have expressed a desire for their parenting identity to be recognized and appropriately engaged with during their treatment. This recognition includes provision of interventions which support them as parents to limit the impact of their mental health on their children. The current study, the first of its kind known to have taken place, details a collaborative intervention development project for parents receiving inpatient care. This project involved the adaptation and extension of a prior parenting-focused course for parents high in anxiety to meet the needs of parents being treated in inpatient settings. In the first two stages of the three-phase project, patients, carers and mental health practitioners contributed to the revision and delivery plan for the course including developing new content for the intervention. In the final stage, which took the form of a participatory evaluation, the intervention was delivered to 11 parents receiving inpatient treatment who then provided extensive feedback. A series of iterative adaptations to the intervention were made in response to this feedback alongside stakeholder input. The final intervention comprises five modules focused on exploring the experience of parents alongside specific learning and skills orientated toward boosting their connection with their children during hospitalisation and in readiness for discharge. Preliminary feedback from patients and ward staff has been positive and the process of delivering the project on inpatient wards was associated with no increase in negative clinical outcomes.